2003
DOI: 10.1159/000069014
|View full text |Cite
|
Sign up to set email alerts
|

Dental Caries Related to Plasma IgG and Alpha<sub>1</sub>-Acid Glycoprotein

Abstract: This study was aimed at determining whether dental caries is associated with induction of the systemic immune system or cytokine response. For this purpose, 85 children from Den Pasar, Bali, Indonesia, aged 6–7 years, were examined clinically and blood plasma was obtained via finger puncture. The concentrations of the acute-phase protein α1-acid glycoprotein (AGP), total IgG and the specific IgG and IgM immunoglobulins against Streptococcus mutans were determined. Immunoelectrophoresis was used for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 11 publications
1
10
0
Order By: Relevance
“…Similar result were observed by Gabryel-Porowska et al, (2014) were role of specific mucin like MUC5B, MUC7 and MUC1 in saliva of children's was compared with dental caries. They showed the role of membrane bound MUC1 and gel forming MUC 5B, which would strengthen epithelial protective barrier and stabilizes mucin in oral cavity for longtime [29][30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…Similar result were observed by Gabryel-Porowska et al, (2014) were role of specific mucin like MUC5B, MUC7 and MUC1 in saliva of children's was compared with dental caries. They showed the role of membrane bound MUC1 and gel forming MUC 5B, which would strengthen epithelial protective barrier and stabilizes mucin in oral cavity for longtime [29][30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…The reason for measuring AGP and CRP was the previous observation where we found a relationship between the acute-phase protein AGP and caries in caries-active children in Indonesia [de Soet et al, 2003]. This was found in a population with a high proportion of dental caries (mean dmft at 6 years 8.8 8 1.9).…”
Section: Discussionmentioning
confidence: 99%
“…A power analyses showed that 69 children per group were needed to determine a significant clinical effect [Van Gemert-Schriks et al, 2008]. Based on an earlier study on AGP in Indonesian children, this group size is large enough to detect differences in acute-phase proteins, when applicable [de Soet et al, 2003]. The participating schools were selected from the database of the Medical Mission.…”
Section: Experimental Designmentioning
confidence: 99%
See 2 more Smart Citations